The distribution of agricultural land and the question of agrarian reform in Brazil - Ceron, A. O. (My University, 1985)
Agrarian reform has long been an acute issue in Brazil, where the distribution of cultivable land is extremely unequal. The Land Statute adopted by the military in 1964 constituted a genuine reform programme, which, however, was never implemented as the government chose to modernize agriculture and expand cultivated areas. This has prevented the poorest from having access to the land.-from English summary